On IP traceback. - Belenky, A. (IEEE Communications magazine)
In this article we present the current state of the art in IP traceback. The rising threat of cyber attacks, especially DDoS, makes the IP traceback problem very relevant to today's Internet security. Each approach is evaluated in terms of its pros and cons. We also relate each approach to practical deployment issues on the existing Internet infrastructure. The functionality of each approach is discussed in detail and then evaluated. We conclude with a discussion on some legal implications of IP traceback.